Zaměstnanecké benefity - Tmejová, Miloslava (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce se zabývá problematikou zaměstnaneckých benefitů z daňového pohledu. Teoretická část obsahuje popis zaměstnaneckých benefitů a jejich daňový dopad při jejich poskytování. Analytická část obsahuje zhodnocení současného systému benefitů ve společnosti SG Equipment Finance Czech Republic, s.r.o. Poslední část bakalářské práce zahrnuje návrhy na zlepšení systému benefitů ve společnosti.

The bachelor thesis deals with employee benefits from a tax perspective. The theoretical part contains a description of employee benefits and their tax effect of the provision of employer to the employee. Analytical part contains an assessment of the current system of benefits in SG Equipment Finance Czech Republic s.r.o. The last part of the bachelor thesis includes suggestions for improving the system of benefits in society.
Employee’s Benefits
Keywords: benefity; výhody; systém benefitů; odměna; motivace; daně; zaměstnanec; zaměstnavatel; benefits; advantages; system of benefits; remuneration; incentives; taxes; employee; employer